Study of the influence of substituent R nature in phenylsulfones derivatives PhSO2R on the chemical shifts of phenyl ring protons in NMR 1H spectra - Mizyuk, Volodymyr; Shibanov, Volodymyr (Publishing House of Lviv Polytechnic National University, 2012)
At the explanation of the spectra peculiarities of phenylsulfones of the general formula C6H5SO2R the arguments in favour of intramolecular influence through the space of functional groups situated in fragment R on the value of phenyl protons chemical shifts δiH have been adduced. При поясненні особливостей ЯМР 1Н спектрів фенілсульфонів загальної формули C6H5SO2R приведено аргументи на користь внутрішньо молекулярної дії через простір функційних груп, розташованих у фрагменті R, на величину хімічних зсувів δiH фенільних протонів.
Вивчення впливу природи замісника R в похідних фенілсульфонів PhSO2R на хімічні зсуви протонів фенільного кільця в ЯМР 1Н спектрах
Keywords: NMR 1H spectrum; phenylsulfone; basic spectral parameter; differential spectral parameters; “threshold”; intramolecular influence; space; ЯМР 1Н спектр; фенілсульфон; базовий спектральний параметр; диференційний спектральний параметр; «поріг»; внутрішньо молекулярна взаємодія; простір